Effect of Austrian COVID-19 lockdowns on acute myocardial infarction frequency and long-term mortality: a multicentre observational study. Issue 2 (8th February 2023) - Mousavi, Roya Anahita; Roth, Dominik; Wallmüller, Christian; Pichler, Gernot; Stratil, Peter; Schreiber, Wolfgang; Delle-Karth, Georg; Schober, Andreas
Abstract : Objectives: The aim of this study was to find out if the decrease in acute myocardial infarction (AMI) admissions during the first COVID-19 lockdowns (LD), which was described by previous studies, occurred equally in all LD periods (LD1, LD2, LD2021), which had identical restrictions. Further, we wanted to analyse if the decrease of AMI admission had any association with the 1-year mortality rate. Design and setting: This study is a prospective observational study of two centres that are participating in the Vienna ST-elevation myocardial infarction network. Participants: A total of 1732 patients who presented with AMI according to the 4th universal definition of myocardial infarction in 2019, 2020 and the LD period of 2021 were included in our study. Patients with myocardial infarction with non-obstructive coronary arteries were excluded from our study. Main outcome measures: The primary outcome of this study was the frequency of AMI during the LD periods and the all-cause and cardiac-cause 1-year mortality rate of 2019 (pre-COVID-19) and 2020. Results: Out of 1732 patients, 70% (n=1205) were male and median age was 64 years. There was a decrease in AMI admissions of 55% in LD1, 28% in LD2 and 17% in LD2021 compared with 2019. There were no differences in all-cause 1-year mortality between the year 2019 (11%; n=110) and 2020 (11%; n=79; p=0.92) or death by cardiac causes [10% (n=97) 2019 vs 10% (n=71) 2020; p=0.983]. Conclusion: All LDs showed a decrease in AMI admissions, though not to the same extent, even though the regulatory measures were equal. Admission in an LD period was not associated with cardiac or all-cause 1-year mortality rate in AMI patients in our study.